2014
DOI: 10.5152/tpa.2014.1209
|View full text |Cite
|
Sign up to set email alerts
|

Iodine, copper, zinc, selenium and molybdenum levels in children aged between 6 and 12 years in the rural area with iodine deficiency and in the city center without iodine deficiency in Hatay

Abstract: Aim: Thyroid diseases related with iodine deficiency are observed commonly in our country and in the world. In this study, we aimed to investigate iodine deficiency in urine and selenium, zinc, copper or molybdenum deficiency which may accompany this in children aged between 6 and 12 years in two schools in the province of Hatay (endemic goitre region). Material and Methods:This study is a case-control field-study in which students aged between 6 and 12 years were included. One hundred fourteen subjects from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Different results were observed for Zn, Se, and I where the mean concentration in goitrous children was found to be lower than those in non-goitrous children. These results corroborate with several authors [4,39].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Different results were observed for Zn, Se, and I where the mean concentration in goitrous children was found to be lower than those in non-goitrous children. These results corroborate with several authors [4,39].…”
Section: Discussionsupporting
confidence: 94%
“…However, recent studies have shown that there are other goitrogen elements such as selenium and zinc [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements conducted immediately after the operation also showed lower serum zinc and The differences between different superscripted letters in the same column are statistically significant (p < 0.05) Table 2 Pre-operative serum element levels of the cases Groups The differences between different superscripted letters in the same column are statistically significant (p < 0.05) Table 4 Post-operative serum element levels of the cases Groups selenium values than the control groups. There are several studies showing a correlation between zinc defect and thyroid hormone levels [16,19,20]. Zinc is an indispensable element in the functioning of 1,5′-deiodinase, which is necessary for the conversion of T 4 to T 3 [6].…”
Section: Discussionmentioning
confidence: 99%
“…Molybdenum deficiency is typically considered a metabolic disease and is characterized by a defect in psychomotor functioning. A correlation has been found between molybdenum and both selenium and iodine (21) . As a component of both tri-iodothyronine (T3) and tetra-iodothyronine (T4) thyroid hormones, iodine is critical for normal thyroid function, and selenium is a cofactor for thyroperoxidase, an enzyme catalyzing the production of these hormones in the thyroid gland.…”
Section: Discussionmentioning
confidence: 89%